Encounters with Kusama: disability, feminism, and the mediated Mad art of #InfiniteKusama - Jerreat-Poole A; Brophy S (Informa UK Limited, 2021)
The 2018 exhibition “Infinity Mirrors” at the Art Gallery of Ontario (AGO) in Toronto, and the accompanying social media phenomenon #InfiniteKusama, harnessed the myth of the “mad genius” who “overcame” hardship in its celebration of the life and work of artist Yayoi Kusama, yet veered away from a nuanced engagement with disability, madness/mental illness, and access. Desiring a crip version of the artist and psychiatric user/survivor, we take up Marta Zarzycka and Domitilla Olivieri’s call to mobilize the feminist potential of affective encounters in digital spaces, generating an analysis of our mediated interactions with Kusama’s persona and artwork at the cultural sites of the art gallery, Instagram, and Twitter. While the physical and digital extensions of the exhibition tried to elicit participation in normative and normalizing ways, critically crip moments of productive tension ruptured the smooth lines of power and ideology in the institution. Through a series of personal reflections we showcase the potential for “affective encounters” between bodies in spaces to disrupt ableist and sanist norms.
Keywords: Social Sciences; Communication; Women's Studies; Critical disability studies; feminist methodology; visual culture; digital media; social media